MicroRNA-9 regulates mammalian axon regeneration in peripheral nerve injury. Issue 1 (May 2017) - Jiang, Jingjing; Hu, Yiwen; Zhang, Boyin; Shi, Yao; Zhang, Jin; Wu, Xiuying; Yao, Peng
Effective axon regeneration is achieved mainly by precise regulation of gene expression after peripheral nerve injury. MicroRNAs play an important role in controlling axon regeneration owe to its key epigenetic function in regulating gene expression. Here, we reveal that microRNA-9 (miR-9) may be a new suppressor of axon regeneration and FoxP1 is the functional target of miR-9. High level of endogenous miR-9 in sensory neurons inhibited axon regeneration in vitro and in vivo. In addition, the regulatory effect of miR-9 was mediated by changes in FoxP1 levels. Full rescuing effect of axon regeneration was achieved by FoxP1 up-regulation. Most importantly, we showed that miR-9-FoxP1 might be a new signaling pathway to regulate mammalian axon regrowth. Moreover, we provided the first evidence that maintaining a higher level of FoxP1 in sensory neurons by the microRNA is necessary for efficient axon regeneration.